Review on 3D growth engineering and integration of nanowires for advanced nanoelectronics and sensor applications. (28th May 2022) - Hu, Ruijin; Yu, Linwei
Abstract: Recent years have witnessed increasing efforts devoted to the growth, assembly and integration of quasi-one dimensional (1D) nanowires (NWs), as fundamental building blocks in advanced three-dimensional (3D) architecture, to explore a series of novel nanoelectronic and sensor applications. An important motivation behind is to boost the integration density of the electronic devices by stacking more functional units in the out-of-plane z- direction, where the NWs are supposed to be patterned or grown as vertically standing or laterally stacked channels to minimize their footprint area. The other driving force is derived from the unique possibility of engineering the 1D NWs into more complex, as well as more functional, 3D nanostructures, such as helical springs and kinked probes, which are ideal nanostructures for developping advanced nanoelectromechanical system (NEMS), bio-sensing and manipulation applications. This Review will first examine the recent progresses made in the construction of 3D nano electronic devices, as well as the new fabrication and growth technologies established to enable an efficient 3D integration of the vertically standing or laterally stacked NW channels. Then, the different approaches to produce and tailor more sophisticated 3D helical springs or purposely-designed nanoprobes will be revisited, together with their applications in NEMS resonators, bio sensors and stimulators in neural system.